DASAR PENAMAAN PERKITARAN KERATON KERAJAAN MATAN TANJUNGPURA KECAMATAN BENUA KAYONG KABUPATEN KETAPANG - Ersa Miranda; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study was to describe the classification of naming, the meaning of naming, and produce a text structure of thematic description of the Royal Palace of Matan Tanjungpura as a supplement for learning Indonesian Class VII based on the naming basis of the circle of the Royal Palace of Matan Tanjungpura, Benua Kayong District, Ketapang Regency. The method used in this study is a descriptive method with a qualitative form. The source of data in this study is the speech of informants who understand the naming of places in the vicinity of the Matan Tanjungpura royal palace, Benua Kayong District, Ketapang Regency. Data collection techniques are observation techniques, interview techniques, note-taking techniques, and recording techniques. Based on all the data that has been analyzed, there are naming bases that can be classified into seven, namely 2 place naming data based on geographical conditions, 6 place naming data based on plants, 2 place naming data based on function, 2 place naming data based on ethnicity, 5 place naming data based on names of people, 5 data for naming places based on stories, and 3 data for naming places based on buildings. The total number of data is 25 data. The meaning of naming consists of 4 types of meaning, namely lexical meaning there are 8 data, grammatical meaning is 9 data, referential meaning is 7 data, and associative meaning is 1 data. This research is related to the 2013 curriculum on Indonesian language subjects in SMP class VII odd semesters which are suggested to be reference material for learning activities at school.Keywords: Basis of naming, Meaning of naming, Royal Palace of Matan Tanjungpura